Faunal dietary response to the Heinrich Event 4 in southwestern Europe - Rivals, Florent (2018)
The dietary traits of the ungulates from the Canyars assemblage (Late Pleistocene; Gavà, Barcelona, Spain) are analysed through tooth mesowear andmicrowear to study their feeding behaviour as well as the climatic conditions during the time of the arrival of the early modern Europeans in the northeast of the Iberian Peninsula. During the Heinrich Event 4 (HE4, between 39 and 40 kyr B.P.), the dietary adaptations of ungulates to grazing dominated the community, and included horses, as well as some red deer, aurochs, and ibex. Results show a rigorous climate, with the presence of grasslands capable of sustaining a high ungulate biomass. The composition of the Canyars ungulate community and its dietary adaptations clearly reveals some particularity of the HE4 in the northeast of the Iberian Peninsula. These open landscapes certainly favoured the migration routes of large mammals along the Mediterranean basin, and also favoured the dispersal of modern humans into the northeast of the Iberian Peninsula.